Reflections on the iberian funerary feasting - García Cardiel, Jorge (ARYS. Antigüedad: Religiones y Sociedades, 2020)
On this paper we will try to question the reality of the Iberian funerary feasting, so we will go through all the archaeological evidences which have been used in order to affirm its actual existence. Our conclusion is that there are some dates which allow us to suspect of the reality of this ritual, but we can’t consider it as a proved thing, and in any case we can accept it as a generalized ritual all over the Iberian culture. We deny also the Greek influence over this kind of feasting: if we accept its existence, we must interpret it as the evolution of a preexistent ritual which dates at least from the Tartesians’ age, with precedents in the Semitic world.
Keywords: Silicernia; Los Villares; El Molar; faunist remains; Mas Castellar de Pontós; Turó dels dos Pins; symposium